MIXED METHODS RESEARCH: MERITS, APPLICATIONS AND CHALLENGES - Josephine Oranga (International Journal of Social Science, 2025)
Mixed methods research is an approach that draws from the strengths of both quantitative and qualitative research methodologies, resulting in richer insights and more robust conclusions. This article, thus, explores the merits, applications and challenges associated the mixed methods approach through a synthesis of studies published between 2006 and 2023. According to this analysis, the advantages of the mixed methods approach include: comprehensive understanding of the research problem, validation of data through triangulation, flexibility and adaptability during the research process, yields rich and contextualized data, provides both depth and breadth to the study and enhances interpretation of findings. On the other hand, some of the challenges are: requires additional financial resources and time, requires one to possess expertise in both qualitative and quantitative approaches, the challenge of integrating qualitative and quantitative data and the challenge of interpreting the findings. This review, thus, concludes that the integration of both qualitative and quantitative approaches is powerful and enables researchers to tap into the strengths of both approaches (qualitative and quantitative), thereby providing a fuller, more nuanced understanding of the phenomena under study